Voltage control of magnetic single domains in Ni discs on ferroelectric BaTiO3. (11th May 2018) - Ghidini, M; Zhu, B; Mansell, R; Pellicelli, R; Lesaine, A; Moya, X; Crossley, S; Nair, B; Maccherozzi, F; Barnes, C H W; Cowburn, R P; Dhesi, S S; et al.
Abstract: For 1 µ m-diameter Ni discs on a BaTiO3 substrate, the local magnetization direction is determined by ferroelectric domain orientation as a consequence of growth strain, such that single-domain discs lie on single ferroelectric domains. On applying a voltage across the substrate, ferroelectric domain switching yields non-volatile magnetization rotations of 90°, while piezoelectric effects that are small and continuous yield non-volatile magnetization reversals that are non-deterministic. This demonstration of magnetization reversal without ferroelectric domain switching implies reduced fatigue, and therefore represents a step towards applications.